2013
DOI: 10.3844/ajavsp.2013.152.158
|View full text |Cite
|
Sign up to set email alerts
|

BIOCHEMICAL AND HEMATOLOGICAL ALTERATIONS IN MICE INOCULATED WITH OUTER MEMBRANE PROTEIN, LIPOPOLYSACCHARIDES AND WHOLE CELLS OF <I>PASTEURELLA MULTOCIDA</I> TYPE B: 2

Abstract: Haemorrhagic septicaemia in cattle and buffaloes is an economically important livestock disease in Asia including Malaysia. Therefore, the aim of this study was to investigate the biochemical and hematological alterations in mice model inoculated with outer membrane protein, lipopolysaccharides and whole cells of Pasteurella multocida type B: 2. Two hundred healthy male mice of eight to ten weeks old were used in this study. The mice were divided into four equal groups of 50 mice each. Mice of group 1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
0
0
Order By: Relevance
“…Oral inoculation of Pasteurella multocida type B: 2 and its LPS into Balb c mice in the present study was able to produce histopathological changes in the vital organs. These findings were similar to those reported in the experimental infection of mice and buffalo calves via oral exposure [15,[26][27][28][29]. However, the use of graded doses of Pasteurella multocida type B: 2 and its LPS as used in this study was not previously reported in mice following oral inoculation.…”
Section: Discussionsupporting
confidence: 92%
“…Oral inoculation of Pasteurella multocida type B: 2 and its LPS into Balb c mice in the present study was able to produce histopathological changes in the vital organs. These findings were similar to those reported in the experimental infection of mice and buffalo calves via oral exposure [15,[26][27][28][29]. However, the use of graded doses of Pasteurella multocida type B: 2 and its LPS as used in this study was not previously reported in mice following oral inoculation.…”
Section: Discussionsupporting
confidence: 92%
“…However, the humoral immune response to LPS varies and is dependent upon the host animal and on variations within the LPS structure (Harper et al, 2011;Hodgson et al, 2013). Although most of experimental infection using LPS of P. multocida B:2 focused on clinical and pathological changes in the respiratory and gastrointestinal tracts (Horadagoda et al, 2002;Abdullah et al, 2013a), less attention has been paid on the nervous system. However, recent study by Jesse et al (2014) demonstrated the ability of LPS of P. multocida B:2 to induce histopathological changes in pituitary gland in male and female mice and finally change the hormonal levels.…”
Section: Virulence Factorsmentioning
confidence: 99%
“…The role of cytokines in the pathogenesis of P. multocida infection has been studied using murine and buffalo models, and a surge in pro-inflammatory cytokines that results in inflammatory reaction in the tissues were attributed in pathogenesis of the disease. In addition, the release of cytokines activates the acute phase response (APR) (Horadagoda et al, 2001;Praveena et al, 2010;Abdullah et al, 2013a). The most notable cytokines are TNFα, IL-1β, IL-6, IL-8 and IL-12 (Eckersall, 2006;Cray et al, 2009).…”
Section: Cytokines and Acute Phase Proteins Effect Due To P Multocida...mentioning
confidence: 99%
See 1 more Smart Citation